Retrospective evaluation of repeated supratherapeutic ingestion (RSTI) of paracetamol†. (3rd August 2019) - Egan, Harry; Isbister, Geoffrey K.; Robinson, Jennifer; Downes, Michael; Chan, Betty S.; Vecellio, Elia; Chiew, Angela L.
Abstract: Background : Repeated supratherapeutic ingestion (RSTI) of paracetamol can result in acute liver injury. Management guidelines vary worldwide and in Australia, acetylcysteine treatment is recommended in patients with a paracetamol concentration ≥20 mg/L and/or alanine transaminase (ALT) ≥50 U/L. Objectives : To investigate patients with RSTI of paracetamol and determine whether admission ALT <50 U/L rules out those who develop hepatotoxicity (ALT >1000 U/L). Method : Retrospective review of paracetamol RSTI presentations to two toxicology services over a four-year period. Patients were included if they ingested >4 g per 24 h of paracetamol for a period >8 h, regardless of intent. Data collected included demographics, ingestion history, pathology results, treatments and outcomes. Results : 266 patients were identified with median ingested dose of 9 g per 24 h (IQR: 6–12 g) over a median of 2 days (IQR: 1–5 days). On presentation, paracetamol was detected in 192 (72%), with median concentration of 14 mg/L (IQR: 7–27 mg/L). Median ALT on admission in those developing hepatotoxicity was significantly higher, 1182 U/L (IQR: 598–4251 U/L), compared to 30 U/L (IQR: 18–59 U/L; p < .0001) in those who did not. All 17 who developed hepatotoxicity had an ALT ≥50 U/L on presentation. Five patients presenting with an ALT <50 U/L developed a peak ALT between 50 and 1000 U/L, of which three had a paracetamol concentration <20 mg/L. 139 (52%) received acetylcysteine, of which 64 received an abbreviated course (<20 h), with a median length of infusion of 11 h (IQR: 7–14 h). 127 (48%) patients were not treated with acetylcysteine, none of these patients returned to hospital. Conclusion s: Our results confirm that those developing hepatotoxicity from RSTI of paracetamol have an elevated ALT on presentation. Presenting ALT <50 U/L appears to be a safe threshold not to administer acetylcysteine, provided the paracetamol concentration is low.